Mediation Opportunities in Settling Divorce Cases Through E-Litigation (Case Study of Judges' Experience in Martapura Class IB Religious Court) - Muhammad Rizal Muharam (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract In the e-litigation trial process the judge cannot meet directly with the parties, so that Article 130 HIR and Article 154 RBg are not maximally realized by the panel of judges in the e-litigation trial. In the non-e-litigation trial process, the judge has the opportunity to meet and reconcile the litigants directly, which often occurs at every stage of the trial. The focus of this research aims to determine the opportunities for mediation in the settlement of divorce cases through e-litigation at the Martapura Class IB Religious Court and what obstacles hinder mediation opportunities in the settlement of divorce cases through e-litigation. This type of research is empirical legal research. Using a qualitative descriptive approach. Mediation opportunities in the settlement of divorce cases through e-litigation at the Martapura Class IB Religious Court are very small. The panel of judges only has mediation opportunities in the settlement of divorce cases through e-litigation at the first trial stage and during the evidentiary hearing. The obstacles that hinder mediation opportunities in the settlement of divorce cases through e-litigation are found in the trial system and the type of case. According to the author, the only way to overcome the obstacle of limited mediation opportunities in the e-litigation trial system is to make peace outside the court. In this case the judge cannot do much, the judge can only invite the parties to reconcile by providing advice and motivation. Keywords: Mediation, Divorce, E-Litigation Abstract Pada proses persidangan secara e-litigasi hakim tidak dapat bertemu secara langsung dengan para pihak, sehingga Pasal 130 HIR dan Pasal 154 RBg tidak terealisasi dengan maksimal oleh majelis hakim pada persidangan secara e-litigasi. Pada proses persidangan non e-litigasi majelis hakim memiliki kesempatan untuk bertemu dan mendamaikan para pihak yang berperkara secara langsung, yang dimana sering terjadi perdamaian pada setiap tahapan persidangan. Fokus penelitian ini bertujuan untuk mengetahui peluang mediasi dalam penyelesaian perkara perceraian melalui e-litigasi di Pengadilan Agama Martapura Kelas IB dan kendala apa saja yang menghambat peluang mediasi dalam penyelesaian perkara perceraian melalui e-litigasi. Jenis penelitian adalah penelitian hukum empiris. Menggunakan pendekatan deskriptif kualitatif. Peluang mediasi dalam penyelesaian perkara perceraian melalui e-litigasi di Pengadilan Agama Martapura Kelas IB sangat kecil. Majelis hakim hanya memiliki peluang mediasi dalam penyelesaian perkara perceraian melalui e-litigasi pada tahapan sidang pertama dan pada saat sidang pembuktian. Adapun kendala yang menghambat peluang mediasi dalam penyelesaian perkara perceraian melalui e-litigasi yaitu terdapat di sistem persidangan dan jenis perkara. Menurut penulis satu-satunya cara untuk mengatasi kendala terbatasnya peluang mediasi dalam sistem persidangan secara e-litigasi adalah dengan melakukan perdamaian diluar pengadilan. Dalam hal ini hakim tidak bisa berbuat banyak, hakim hanya dapat mengajak para pihak untuk berdamai dengan memberikan nasihat dan motivasi. Katakunci: Mediasi, Perceraian, E-Litigation